2000
DOI: 10.1309/0q7f-qtgm-6dpd-tlgy
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Subclassification of Primary and Recurrent Lymphoma

Abstract: The primary diagnosis of non-Hodgkin lymphoma/leukemia by fine-needle aspiration (FNA) is still controversial and relatively underused. We evaluated our FNA experience with lymphomas using the revised European-American classification of lymphoid neoplasms to determine the reliability of FNA when combined with flow cytometry in the diagnosis of lymphoma, the types of diagnoses made, and the limitations of this technique. Slides and reports from all lymph node and extranodal FNAs performed during the period Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(53 citation statements)
references
References 9 publications
1
45
0
6
Order By: Relevance
“…Fine needle aspiration (FNA) biopsy is widely used to diagnose malignant neoplasms, but its role in diagnosing lymphoma is still controversial. 43,44 Because the revised REAL/WHO classification is based on both morphology and immunophenotyping, FNA alone is not acceptable as a reliable diagnostic tool for NHL. However, its use in combination with ancillary techniques may provide precise diagnosis, thereby obviating the need for a more invasive biopsy.…”
Section: Diagnosismentioning
confidence: 99%
“…Fine needle aspiration (FNA) biopsy is widely used to diagnose malignant neoplasms, but its role in diagnosing lymphoma is still controversial. 43,44 Because the revised REAL/WHO classification is based on both morphology and immunophenotyping, FNA alone is not acceptable as a reliable diagnostic tool for NHL. However, its use in combination with ancillary techniques may provide precise diagnosis, thereby obviating the need for a more invasive biopsy.…”
Section: Diagnosismentioning
confidence: 99%
“…Some criteria include a ĸ/λ ratio of 3 or more, or a λ/ĸ ratio of 2 or more. Others include a ratio of 6 or more [2,3,4,6,8,11,12,13,14,15]. Sneige et al [5] performed immunostaining using fine-needle aspiration samples and regarded lesions with an LCR ratio of 6 or more as monoclonal or B cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one of the reasons why LCR could not be detected on FCM is the fragility of large lymphoma cells [14,16,17]. Verstovsek et al [18] reviewed patients with false-negative reactions on FCM and found that 27% of patients with DLBCL showed false-negative reactions on FCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the diagnosis of lymphoma is becoming increasingly dependent on knowledge of the immunophenotype as well as on molecular and cytogenetic findings [6], cytomorphology alone is insufficient for the diagnosis of lymphoproliferative disorders. Newer techniques such as immunophenotyping, cytogenetics, ploidy analysis and molecular studies, however, have opened promising avenues for the initial diagnosis of NHL on small samples [7,8,9,10], and numerous studies performed over the past 20 years have shown FNA to have both a high sensitivity and a high specificity in the diagnosis of NHL when used with ancillary techniques [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. When FNA cytomorphology is combined with FC on a sample from any organ and the findings are compared with follow-up surgical specimens, diagnostic sensitivity and specificity have been reported to be as high as 97 and 94%, respectively [5].…”
Section: Introductionmentioning
confidence: 99%